Изучение интерференции русского и латышского языков в свете методологии У. Вайнрайха - Stoikova, Tatiana (Przegląd Rusycystyczny, 2018)
Studying of an interference of the Russian and Latvian languages in the light of methodology of U.Weinreich In article on the basis of Weinreich’s methodology are generalized and are systematized the phenomena of the Latvian-Russian and the Russian-Latvian phonetic interference, interference zones are predicted. At the heart of methodology – typology of a phonetic interference, offered by U.Weinreich. The typology includes four types of an interferntion: insufficient differentiation of phonemes, superdifferentiation of phonemes, reinterpretation of distinctions, substitution of sounds. The typology can be applied as the effective tool to linguistic studying of an interference of any two the contacting languages.